Glorious rivals - Barnes, Jennifer Lynn (Barnes, Jennifer Lynn. Grandest Game (Series), 2025)
"Players move into the next round of the Grandest Game, where millions of dollars in prize money are on the line-and new relationships, motivations, and threats come to light. Seven players arrived on Hawthorne Island, each with their own secrets and motivations to win the Grandest Game. Millions are at stake, but so are hearts--and lives. The players now must race to win the game, solve myriad mysteries, and survive the twists and turns of Glorious Rivals"--